Experimental Optimization of Metal Foam Structural Parameters to Improve the Performance of Open-Cathode Proton Exchange Membrane Fuel Cell - Wang, Zixuan; Fan, Linhao; Wu, Siyuan; Tongsh, Chasen; Zhang, Yanyi; Yang, Zirong; Du, Qing; Hao, Dong; Zhou, Feikun; Jiao, Kui (Frontiers in Thermal Engineering, 2022)
Using metal foam as a flow field structure is an attractive route to improve the performance of open-cathode PEMFC. Metal foam has shown great potential in improving the uniformity of reactants, but optimized structure parameters that can more effectively transfer gas and remove excess water are needed. Here we experimentally investigate the effect of metal foam structure parameters on cell performance using polarization curves, power density curves, and electrochemical impedance spectrum (EIS) measurements. By optimizing the pore density, thickness, and compression ratio of the metal foam, the performance of the fuel cell is improved by 49.8%, 42.1%, and 7.3%, respectively. The optimum structure value of metal foam is the pore density of 40 PPI, the thickness of 2.4 mm, and the compression ratio of 4:2.4. In this configuration, the cell could achieve a maximum power density of 0.485 W cm−2. The findings of this work are beneficial for the application of metal foams in open-cathode PEMFC.